ANALISIS KOMPARASI RELEVANSI NILAI INFORMASI AKUNTANSI SEBELUM DAN SESUDAH KONVERGENSI IFRS DI INDONESIA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2011-2012) - Syagata, Gupitasari Syahbi; Daljono, Daljono (Diponegoro Journal of Accounting, 2014)
This study aimed to test whether there is an increase in the value relevance of accounting information after the convergence of IFRS in Indonesia. The value relevance of accounting information can be seen on the effect of earnings, equity book value, and operation cash flow in the decision-making of investors as reflected in the stock price. This research was an empirical study with purposive sampling technique in data collection. Data were obtained from secondary data manufacturing company’s financial statements during period 2011 through 2012. The sample consisted of 75 listed company each year. The data were analyzed using multiple regression analysis and Chow test analysis The result of this study showed that there were an increasing in the value relevance of accounting information after convergence of IFRS in Indonesia. This chow test result showed that there were deference between the value relevance of accounting information before and after the convergence of IFRS in Indonesia.